The Giant Monopole and Dipole Resonances within the Constrained Molecular Dynamics (CoMD) Framework - Depastas, Teo; Souliotis, Georgios; Palli, Konstantina; Bonasera, Aldo; Zheng, Hua (HNPS Advances in Nuclear Physics, 2022)
The Constrained Molecular Dynamics (CoMD) model is used to describe the collective motion of various nuclear systems. A CoMD-inspired phenomenology for the GDR is developed. In addition, the dependence of the GDR upon the effective interaction parameters is studied. Furthermore, both the monopole and dipole main and soft modes of 68Ni are reliably reproduced. We conclude that a hard EoS with K=308 MeV increases the GDR energy, without altering the GMR energy. Thus, this EoS gives rather consistent results in both the monopole and dipole giant resonances.